2017
DOI: 10.4000/paleo.3075
|View full text |Cite
|
Sign up to set email alerts
|

Le site stratifié du Bois Clair à Montguyon (Charente-Maritime, France) : récurrences paléolithiques, brièveté des occupations et aires de débitage spécialisées

Abstract: site stratifié du Bois Clair à Montguyon (Charente-Maritime, France) : récurrences paléolithiques, brièveté des occupations et aires de débitage spécialisées »,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, they further exploited the parts of the block of the highest quality, creating a specific variant of the Levallois production sequence to overcome the costs of raw material quality and to exploit a single resource for knapping methods with a high and low degree of control on final products . Moreover, stone tool refits allow for the identification of which blanks a knapping procedure is mainly designed for and the recognition of the variability in the technical procedures that were applied to achieve these technological goals (Bachellerie et al 2007;Bernard-Guelle et al 2017; Ortiz Nieto-Márquez and Baena Preysler 2017). Recent studies have shown a great variability in the economic behaviours hidden in the concept of ramification in the Middle Palaeolithic, and these behaviours respond to the different strategies that led the choices regarding which tools will circulate as personal gear and why (Romagnoli et al 2018b;Turq et al 2013).…”
Section: Refits: Still a Privileged Methods For Understanding And Intementioning
confidence: 99%
“…In addition, they further exploited the parts of the block of the highest quality, creating a specific variant of the Levallois production sequence to overcome the costs of raw material quality and to exploit a single resource for knapping methods with a high and low degree of control on final products . Moreover, stone tool refits allow for the identification of which blanks a knapping procedure is mainly designed for and the recognition of the variability in the technical procedures that were applied to achieve these technological goals (Bachellerie et al 2007;Bernard-Guelle et al 2017; Ortiz Nieto-Márquez and Baena Preysler 2017). Recent studies have shown a great variability in the economic behaviours hidden in the concept of ramification in the Middle Palaeolithic, and these behaviours respond to the different strategies that led the choices regarding which tools will circulate as personal gear and why (Romagnoli et al 2018b;Turq et al 2013).…”
Section: Refits: Still a Privileged Methods For Understanding And Intementioning
confidence: 99%